A new maximum power point estimator control strategy to maximize output power of the double stator permanent magnet generator - Misron, Norhisam; Vaithilingam, Chockalingam Aravind; Mailah, Nashiren Farzilah; Masaya, Kudo; Hanamoto, Tsuyoshi (MDPI, 2016)
A new control estimator to maximize the power generated with a maximum power point estimator is introduced. The power mapping characteristics from the double-stator generator are modeled as a mathematical equation which is used to develop the estimator for maximum power tracking to maximize the generated power. The proposed estimator automatically traces the instantaneous maximum power at various load conditions. However, to stabilize the output voltage, a boost converter is used from the inverter side. The developed double-stator generator is tested with the new estimator for the maximizing power generation capability under laboratory conditions. The experimental results confirm that with the new estimator, the average power generation capability is increased by 12% and the peak value is increase by 22%.